ESTERIFIKASI DAN DEASIDIFIKASI MINYAK JELANTAH PADA PEMBUATAN BIODIESEL MENGGUNAKAN KATALIS ABU TONGKOL JAGUNG - Adu, R. E. Y. (Jurnal Kimia (Journal of Chemistry); Vol. 14, No. 2 Juli 2020, 2020)
Esterification and deacidification of waste cooking oil using alkali neutralization for biodiesel production using corncob ash as an alternative base catalyst was carried out. This study aimed to attainone of the desired transesterification conditionsby reducing free fatty acids content of waste cooking oil. Esterification was carried out by reacting waste cooking oil and methanol with certain volume ratio and acid catalyst (H 2 SO 4 ) at 50 o C for 4 hours. Deacidification was carried out by adding 0.5 N NaOH solution (15% excess alkali) at 60 o C for 30 minutes. Esterification of waste cooking oil using acid catalyst before transesterification with corn cobs ash catalyst significantly increased the efficiency of free fatty acid conversion (92.69%) under volume ratio of 25% methanol /oil and 0.5% acid catalyst for 4 hours reaction. Deacidification of esterified oil with FFA content of 2.29 mg KOH /g oil through alkali neutralization at 55 o C using alkaline content of 0.8 N reduces free fatty acid content to 0.47 mg KOH /g oil. Transesterification results showed that biodiesel component of waste cooking oil was dominated by polyunsaturated fatty acids (linoleic acid / C 18-2 ), monounsaturated fatty acids (palmitic acid / C 16-1 and oleic acid / C 18-1 ) and saturated acids (palmitic / C 16-0 and stearic acid / C 18-0 ). Most of the biodiesel products were similar to those of the diesel physical characters. Biodiesel made of waste cooking oil meets the biodiesel quality standard (SNI 7182: 2015) for such parameters of density, viscosity, acid number, saponification value, iodine number and cetane. Esterification and neutralization process are effective in reducing free fatty acids content of waste cooking oil before being used in transesterification with corn cobs ash catalyst. Keywords: esterification, neutralization, alkali, waste cooking oil, biodiesel, corn cobs ash